Hip Adduction and Abduction Strength Profiles Among Bantam, High School, Juniors, and Collegiate American Ice Hockey Players - Morgan L. Olson; Gary Schindler (North American Sports Medicine Institute, 2022)
# Background Adductor strains are the most common non-contact musculoskeletal injury sustained in ice hockey. Systematic reviews have determined higher level of play and lower hip adduction to abduction strength ratios to be associated with an increased risk of adductor strain across multiple sports. Limited research exists regarding hip adduction and abduction strength profiles across various levels of ice hockey players. # Purpose To compare isometric hip adduction and abduction strength profiles among bantam, high school, tier one juniors, and NCAA Division I collegiate ice hockey players. A secondary purpose was to identify whether differences in strength profiles between dominant and non-dominant limbs exist. # Study Design Cross-sectional cohort study. # Methods A questionnaire of demographic data, hockey, and injury specific information was completed by all subjects. The mean of three reps of maximal hip isometric adduction and abduction strengths were quantified using a handheld dynamometer with external belt-fixation. Ratios of hip adduction-to-abduction strength were calculated and normalized for body weight. # Results A total of 87 uninjured skaters were included in this study with a mean age of 17 years. Mean hip adductor-to-abductor ratios for Bantam hockey players were 121% followed by collegiate (115%), Juniors (111%), and high school (109%) hockey players. No statistically significant differences were found between peak hip adduction and abduction isometric strength and playing level. In addition, there was no difference between unilateral hip strength ratios and shooting hand or leg dominance. While 34.5% of subjects reported a history of adductor injury, no significant differences existed regarding strength ratios during bilateral comparison or when compared to their team norms. Three subjects were found to have unilateral ratios of less than 80%, while two subjects demonstrated bilateral ratios of less than 80%. # Conclusions Symmetry is illustrated between dominant and non-dominant legs in ice hockey players with and without a history of adductor injury. Results align well with previously established cross-sectional data from Australian football, with ratios of 103% in high school players, 107% in semi-professional players, and 113% in collegiate players. # Level of Evidence Level 3